Factors Influencing the Success of Learning Management in Enhancing Scientific Literacy Among High School Students in the Three Southernmost Provinces - Hayibaka, Muhammadkhoiri; Adulyasas, Lilla; Anantanukulwong, Roseleena; Lateh, Afifi (Journal of Information and Learning [JIL], 2025)
This research aimed 1) to study the factors that play a role in promoting the success of science learning management to enhancing scientific literacy among high school students in the three southernmost provinces of Thailand, and 2) to analyze the relationships and influences of factors affecting the success of science learning management to enhancing scientific literacy among high school students in the three southernmost provinces. The study employed a mixed-methods approach with an exploratory sequential design, divided into two phases. In the first phase, qualitative research methods were employed. The research tool was a semi-structured interview. Key informants included eight secondary school science teachers, three university lecturers, and two scientists, totaling 13 participants. From the perspectives of these key informants, factors that promote the success of science learning management to enhancing scientific literacy were identified in five areas: instructional management, students’ learning behaviors, administrative support, curriculum analysis and design, and assessment and evaluation. In the second phase, quantitative research methods were used. The research instrument was an opinion questionnaire. The sample consisted of 283 secondary school science teachers under the jurisdiction of the Secondary Educational Service Area Office in the three southern border provinces. The findings revealed that the factors most influencing the success of science learning management to enhancing scientific literacy, ranked in order, were instructional management (r = .804), students’ learning behaviors (r = .675), and administrative support (r = .548). Together, these three factors predicted scientific literacy at a level of 66.80%.